Prediction on Mechanical Properties of Fly Ash Reinforced Polymer Composite Material - A. Yousif, Ban (Al-Nahrain Journal of Science, 2022)
Fly ash with different weight ratios was used as a reinforcing material for the composite material (polyester + 5% short carbon fiber) to make a hybrid composite material. The weight ratio of the carbon fiber used with the polymer was constant, and the weight ratios used for fly ash were (5%, 10%, 15%) wt. The mechanical properties of the hybrid composite material were studied and compared with the composite material without the addition of fly ash. The results showed an increase in the tensile strength and modulus of elasticity by increasing the weight percentage of fly ash, while there was no significant increase in the compressive strength value except for the composite material reinforced by 15% of fly ash. The results showed a significant improvement in the measured mechanical properties of the hybrid composites samples with an increase in the addition percentage of fly ash.